The Gender-Specific Determinants of Labour Supply in Rural and Urban Contexts: Evidence from Armenia’S Transition Economy - Chirkova, S (Springer Singapore, 2021)
The subject of this chapter is gender-specific determinants of labour supply in Armenia. Using the repeated cross-section Armenian Integrated Living Conditions Survey for 2004–2016 the study estimates the likelihood of female and male employment, controlling for a rich set of socio-demographic characteristics. It particularly looks at the relationship between the presence of children and the employment outcomes of parents. The results demonstrate that the presence of children is positively associated with men being in employment. This is also true for mothers in rural areas, but not, interestingly, for mothers in urban areas, where the estimated effect is negative. The magnitude of the effect increases with the number of children, preserving both the sign and statistical significance. The results suggest that rural families with children are more likely to conform to the dual-earner model; while those living in cities tend to follow the more traditional single breadwinner model. © Springer Nature Singapore Pte Ltd. 2021. All rights are reserved.